X-ray perception: Animal studies of sensory and behavioral responses to X-rays - Mantraratnam, Vaishnavi; Bonnet, Jorge; Rowe, Caleb; Janko, Daniel; Bolding, Mark (Frontiers in Cellular Neuroscience, 2022)
Since their discovery in 1895, many studies have been conducted to understand the effect of X-rays on neural function and behavior in animals. These studies examined a range of acute and chronic effects, and a subset of studies has attempted to determine if X-rays can produce any sensory responses. Here we review literature on animal behavioral responses to X-rays from 1895 until 2021 to assess the evidence for detection of X-rays by sensory receptors in animals. We focus on the changes in appetitive and consummatory behavior, radiotaxis, behavioral arousal, and olfactory responses to X-rays that have been reported in the literature. Taken together, the reviewed literature provides a large body of evidence that X-rays can induce sensory responses in a wide variety of animals and also suggests that these responses are mediated by known sensory receptors. Furthermore, we postulate the role of reactive oxygen species (ROS), the most biologically active byproduct of X-rays, as a key mediator of sensory receptor responses to X-rays.